Shifting waters: the challenges of transitioning from freshwater to treated wastewater irrigation in the northern Jordan Valley - Tawfik, Mohamed Hassan; Al-Zawaidah, Hadeel; Hoogesteger, J.; Al-Zu’bi, Maha; Hellegers, Petra; Mateo-Sagasta, Javier; Elmahdi, A. (MDPI, 2023)
Jordan’s water scarcity prompted a national plan whereby treated wastewater is utilized to amend agricultural irrigation water so as to reallocate freshwater to urban/domestic uses. The policy, however, has engendered farmers’ resistance in the Northern Jordan Valley (NJV), causing a stalemate in putting new infrastructure into operation. This research investigated the socio-economic causes of farmer resistance and contestation, and examined the government’s institutional approach to overcome the challenges. We found that the perceived risks of wastewater reuse such as salinization and restrictions from international markets figure prominently in the farmers resistance. As yet, farmers have managed to avoid the shift to treated wastewater use by using the political agency of elite farmers who control the Water Users Associations. These same farmers have adopted informal water access practices to overcome freshwater shortages. At the same time, small producers who don’t have possibilities to access extra water and with less political clout seem more willing to irrigate with treated wastewater. We conclude that understanding the heterogeneous context in which the envisioned wastewater users operate is key to predicting and solving conflicts that arise in treated wastewater reuse projects.